The Dispersal of Genetically Modified Crops Throughout the Ecosystem (International Journal of Food and Nutritional Sciences, 2022)
Despite many potential promises, there is a plethora of worries regarding the effect of GM crops on the environment. Key problems in the environmental evaluation of GM crops include potential invasiveness, vertical or horizontal gene flow, other ecological consequences, effects on biodiversity and the impact of presence of GM material in other goods. These are all extremely multidisciplinary and complicated problems. A key component for a successful evaluation is establishing the right baseline for comparison and decision. For GM crops, the best and most properly defined reference point is the effect of plants produced through conventional breeding. The latter is an essential and recognized component of agriculture. In many cases, the potential effects found for GM crops are remarkably comparable to the implications of new cultivars produced through conventional breeding. When evaluating GM crops compared to current cultivars, the enhanced knowledge base underlying the development of GM crops will offer more confidence in the assurances plant science can provide on the dangers of releasing such crops.